Antibiotic resistance contamination in four Italian municipal solid waste landfills sites spanning 34 years. (March 2021) - He, Pinjing; Huang, Jinghua; Yu, Zhuofeng; Xu, Xian; Raga, Roberto; Lü, Fan
Abstract: Municipal solid waste landfill is now recognized as a significant reservoir of antibiotics and antibiotic resistance genes (ARGs). This study investigates the contamination of antibiotics resistance, in 10 leachate samples collected from four MSW landfills in north Italy spanning 34 years, including ARGs as well as mobile genetic element (MGEs). Antibiotics (0-434740 ng/L) and ARGs (5.56-6.85 × 10 5 copies/μL leachate) were found in leachate. Abundances of the measured ARGs were found to be clustered into two groups with different changing tendencies with landfilling age in different landfills. Even though some antibiotics were banned or limited in Italy, they were found to still occur in landfills and drive the long-term contamination of ARGs indirectly, indicating the persistence of antibiotic resistance. What's more, the complexity of antibiotic resistance in leachate was found to synthetically relate to antibiotics, metals, microbes and MGEs presenting that Mn, SMX and EFC influence positively (p < 0.01) the contamination of tet W, tet Q, tet M, tet A, erm B, and cat, contributing importantly in new leachate. This study discusses the AR pollution of leachate in Italy where antibiotics are used the most in Europe, less reported in literatures. Our results suggest that a full-scale view for landfill antibiotics resistance should be considered with history of landfills, use of antibiotics and different phase in landfills, with both "relative static" and "dynamic tracking" perspective to focus on the principal antibiotic-resistance pollutants for leachate treatment, and raise the attention for landfill post-closure care and landfill mining. Graphical abstract: Image 1 Highlights: ARGs in leachate were grouped into increasing and decreasing with landfill ages. 9 ARGs and 1 MGE were all detected in leachate spanning 34 years. Aging leachate and landfill mining have potential risk of antibiotic resistance. Landfill age and nature of leachate led to the complexity of antibiotic resistance. A full-scale view of period is important for landfill remediation and treatment.